Conservation Drones : mapping and monitoring biodiversity - Wich, Serge A.; Koh, Lian Pin, 1976- (Oxford ; New York, NY : Oxford University Press, 2018)
This book aims to further build capacity in the conservation community to use drones for conservation and inspire others to adapt emerging technologies for conservation.
Deciding to use a drone -- Typology and anatomy of drones -- Sensors -- Surveillance -- Mapping -- Animal detection -- Data post processing -- Future casting.
Includes bibliographical references (pages 97-113) and index.
Keywords: Environmental impact analysis -- Technological innovations; Biodiversity -- Monitoring -- Technological innovations; Drone aircraft -- Scientific applications; Biodiversity conservation -- Technological innovations; Biodiversity -- Remote sensing; Biodiversity conservation -- Evaluation; Biodiversity; Biodiversity conservation -- Evaluation; Drone aircraft; Environmental impact analysis